HASRAT DIAN PURNOMO PADA TOKOH UTAMA DALAM NOVEL PEREMPUAN YANG MENANGIS KEPADA BULAN HITAM: KAJIAN PSIKOANALISIS JACQUES LACAN - Rahmadani, Febrieza; Zurmailis; Maizufri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study analyzes the novel Perempuan yang Menangis kepada Bulan Hitam by Dian Purnomo using a Lacanian psychoanalytic approach to understand the formation of the main character, Magi Diela's, subjectivity within a patriarchal social structure. Using Lacanian concepts such as lack, desire, objet petit a, and the realms of The Real, The Symbolic, and The Imaginary, this research reveals the process of patriarchy's internalization in women and how desire and resistance to symbolic structures create change in the main character. The method employed is a deep textual analysis of symbolism, language, and narrative within the novel. The findings show that the novel is more than just a story of suffering; it is also a medium for resistance against gender injustice, with Magi Diela serving as an example of a woman challenging the patriarchal order. In conclusion, through a Lacanian approach, the novel illustrates how desire serves as the main driving force in a woman's struggle to form a subjectivity free from patriarchal oppression.